2016
DOI: 10.15376/biores.11.1.2403-2416
|View full text |Cite
|
Sign up to set email alerts
|

Delignification Kinetics of Corn Stover with Aqueous Ammonia Soaking Pretreatment

Abstract: Soaking aqueous ammonia (SAA) pretreatment of corn stover was carried out at three temperatures (30, 50, and 70 ºC) and three concentrations of ammonia solution (5, 15, and 25 wt.%). The delignification kinetic model, based on three first-order reactions, was applied to describe the kinetic behavior of lignin removal from corn stover during SAA pretreatment. The first, second, and third terms were based on the initial, bulk, and residual phases of delignification, respectively. The results showed that the mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
3
6
0
Order By: Relevance
“…In this study, 180 °C was considered a suitable pretreatment temperature. This finding is in agreement with previous research, which showed that temperature affected DS value [22].…”
Section: Figuresupporting
confidence: 94%
“…In this study, 180 °C was considered a suitable pretreatment temperature. This finding is in agreement with previous research, which showed that temperature affected DS value [22].…”
Section: Figuresupporting
confidence: 94%
“…As seen for the same pretreatment time and temperature for 1 w/w % NaOH pretreatment, the concentration of lignin in solution increased with time and temperature for 3 w/w% NaOH pretreatment; this is supported by the results obtained by Wongwatanapaiboon et al [13], although, in their work, ammonia was used to pretreat Napier grass. Here, the highest quantity of lignin removed from the Napier grass sample was recorded at 120°C and after 90 mins Fig.…”
Section: Delignification Kinetics Of 3 W/w% Naohsupporting
confidence: 71%
“…In a recent study, the kinetics of lignin removal from corn Stover was carried out by soaking the biomass in different concentrations of aqueous ammonia aided by thermal treatment between 30 and 70°C [13]. Also, the pretreatment of corn Stover was conducted at temperatures of 170-230°C and 150-210°C using hot water and dilute acid to remove lignin from the substrate and it was discovered that pretreatment conditions from 200-230°C did not enhance lignin removal from the biomass [14].…”
Section: Introductionmentioning
confidence: 99%
“…The intended fraction of raw material (biomass with 7% moisture content was used in a quantity equal to circa 20 g of an absolutely dried material) was placed in a stainlesssteel reactor with the capacity of 250 mL, and either 15% or 20% (w/w) ammonia solution was added in order to apply a solid:liquid ratio of 1:12.5. The pretreatment conditions were based on previous research and selected for their preferable delignification ability (Gao et al 2016). The reactor was placed in oil bath that was pre-set and subsequently maintained at 50 °C or 90 °C for 20 h after the load inside the reactor reached the set temperature, and then it was cooled rapidly.…”
Section: Saa Pretreatmentmentioning
confidence: 99%
“…Additionally, aromatic acids or phenolic compounds, which also can have inhibitory effect on enzymes, may be formed as a result of lignin degradation during alkali pretreatment. The notable advantage of the SAA method is that ammonia used in the pretreatment may be recycled from the effluent and reused (Gao et al 2016). However, the long treatment time, high concentration of the base, and formation of residual salts in biomass are some of the flaws of alkali treatment (Verardi et al 2012).…”
Section: Introductionmentioning
confidence: 99%